Beclin-1 knockdown shows abscission failure but not autophagy defect during oocyte meiotic maturation. Issue 12 (17th June 2016) - You, Seung Yeop; Park, Yong Seok; Jeon, Hyuk-Joon; Cho, Dong-Hyung; Jeon, Hong Bae; Kim, Sung Hyun; Chang, Jong Wook; Kim, Jae-Sung; Oh, Jeong Su
ABSTRACT: Cytokinesis is the final step in cell division that results in the separation of a parent cell into daughter cells. Unlike somatic cells that undergo symmetric division, meiotic division is highly asymmetric, allowing the preservation of maternal resources for embryo development. Beclin-1/BECN1, the mammalian homolog of yeast Atg6, is a key molecule of autophagy. As part of a class III phosphatidylinositol 3-kinase (PI3K-III) complex, BECN1 initiates autophagosome formation by coordinating membrane trafficking. However, emerging evidence suggests that BECN1 regulates chromosome segregation and cytokinesis during mitosis. Thus, we investigated the function of BECN1 during oocyte meiotic maturation. BECN1 was widely distributed during meiotic maturation forming small vesicles. Interestingly, BECN1 is also detected at the midbody ring during cytokinesis. Depletion of BECN1 impaired the cytokinetic abscission, perturbing the recruitment of ZFYVE26 at the midbody. Similar phenotypes were observed when PI3K-III activity was inhibited. However, inhibition of autophagy by depleting Atg14L did not disturb meiotic maturation. Therefore, our results not only demonstrate that BECN1 as a PI3K-III component is essential for cytokinesis, but also suggest that BECN1 is not associated with autophagy pathway in mouse oocytes.